2013
DOI: 10.1182/blood-2012-11-466862
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of arsenic trioxide followed by autologous hematopoietic cell transplantation for relapsed acute promyelocytic leukemia

Abstract: Key Points• We conducted a phase 2 study of ATO followed by autologous HCT for relapsed APL.• This sequential treatment is effective and feasible.The optimal treatments for relapsed acute promyelocytic leukemia (APL) remain equivocal. We conducted a phase 2 study to evaluate the efficacy and feasibility of a sequential treatment consisting of induction and consolidation with arsenic trioxide (ATO), peripheral blood stem cell (PBSC) harvest after high-dose cytarabine chemotherapy, and autologous hematopoietic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 32 publications
1
53
1
2
Order By: Relevance
“…(9) A recent prospective study of our JALSG also observed a relatively low relapse rate, in which there were only three relapses among 23 auto-grafted patients with molecular remission at the time of stem cell harvest (5-year EFS rate, 65%). (14) These studies show a prognostic importance of MRD negativity using molecular analysis before HSCT on the outcome. However, the results of the present study differ from previous report in that the MRD negativity is well associated with the low relapse rates in auto-HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(9) A recent prospective study of our JALSG also observed a relatively low relapse rate, in which there were only three relapses among 23 auto-grafted patients with molecular remission at the time of stem cell harvest (5-year EFS rate, 65%). (14) These studies show a prognostic importance of MRD negativity using molecular analysis before HSCT on the outcome. However, the results of the present study differ from previous report in that the MRD negativity is well associated with the low relapse rates in auto-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…(6,9) Recently, in a phase 2 prospective study, our Japan Adult Leukemia Study Group (JALSG) reported the efficacy of sequential treatment using ATO followed by auto-HSCT for 25 patients with relapsed APL. (14) However, evidence has been lacking in terms of the role of auto-HSCT alone on the cumulative relapse rate or efficacy for patients with APL in CR2 who were ineligible for the phase 2 study regimens. Moreover, in situations where no guidelines regarding the optimal choice of auto-or allo-HSCT in CR2 have been determined, the role of HSCT alone in post-remission therapies for patients with APL in CR2 is yet to be evaluated.…”
mentioning
confidence: 99%
“…cytarabine 16 g/m 2 over 4 days followed by PBSC mobilization with G-CSF beginning at day 6, as described previously. 17 A minimum CD34+ cell collection of 2x10 6 per kg was required. The conditioning regimen consisted of BU 12 mg/kg PO divided into 12 doses and melphalan 140 mg/m 2 divided into 2 doses.…”
Section: Methodsmentioning
confidence: 99%
“…Patients in the JALSG cohort were enrolled at 20 centers between December 2005 and June 2009, with data collected prospectively upon study entry, as previously reported. 17 Autologous HSCT Patients at UCSF underwent consolidation with i.v. cytarabine 16 g/m 2 and etoposide 40 mg/kg over 4 days, followed by PBSC mobilization with G-CSF 10 μg/kg per day and PBSC collection upon neutrophil recovery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation